PENERAPAN DERAJAT LUKA RINGAN KORBAN KECELAKAAN LALU LINTAS DI KABUPATEN SIAK - Sinaga, Candra Herianto; Ardiansah; Kadaryanto, Bagio (The Juris, 2024)
In Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation, accidents are also divided into several levels/categories regulated in Article 229 of Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation concerning Road Traffic and Transportation, including: Minor Traffic Accidents (an accident that results in damage to vehicles and/or goods). The purpose of this research is to analyze the application of degrees of minor injuries to traffic accident victims in Siak Regency based on the Law of the Republic of Indonesia Number 22 of 2009 concerning Traffic and Road Transport regarding traffic, to analyze obstacles and efforts to overcome obstacles in the application of degrees of minor injuries to victims. Traffic Accidents in Siak Regency Based on Law of the Republic of Indonesia Number 22 of 2009 concerning Traffic and Road Transport Concerning Traffic. The method used is sociological legal research. Based on the research results, it is known that the application of degrees of minor injuries to traffic accident victims in Siak Regency based on the Law of the Republic of Indonesia Number 22 of 2009 concerning Traffic and Road Transport regarding traffic has not been implemented optimally because the application of degrees of minor injuries is only regulated in the law. Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation concerning Road Traffic and Transportation, while the application of degrees of minor medical injuries is not regulated in Law Number 17 of 2023 concerning Health or the New Criminal Code.